2021
DOI: 10.18280/isi.260302
|View full text |Cite
|
Sign up to set email alerts
|

Web Usability Testing on Diabetic Retinopathy Consultation System

Abstract: This article presents an investigation on the usability testing of Diabetic Retinopathy Consultation System (DRCS) development. DRCS is an interactive medical web-based consultation system for diabetic retinopathy screening with the features of image processing and image editing. The expected outcome of this paper is a comprehensive analysis of the web usability towards the development of a novel consultation system for diabetic retinopathy screening. Seven important usability evaluation components were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…( It was reported that the usability testing result showed that the native G-MoMo applications were highly efficient because mobile money subscribers could take less time to complete the given tasks accurately (Lynn et al, 2020;Byun et al, 2020;Hussain et al, 2020;Zakaria et al, 2020;Sukmasetya et al, 2020;Tyas & Khairunisa, 2020;Emanuela et al, 2020;Mubeen et al, 2020;A'bas et al, 2021;Putri et al, 2021).…”
Section: Heuristic Evaluation and Usability Testingmentioning
confidence: 99%
“…( It was reported that the usability testing result showed that the native G-MoMo applications were highly efficient because mobile money subscribers could take less time to complete the given tasks accurately (Lynn et al, 2020;Byun et al, 2020;Hussain et al, 2020;Zakaria et al, 2020;Sukmasetya et al, 2020;Tyas & Khairunisa, 2020;Emanuela et al, 2020;Mubeen et al, 2020;A'bas et al, 2021;Putri et al, 2021).…”
Section: Heuristic Evaluation and Usability Testingmentioning
confidence: 99%